Effect of Sodium Starch Glycolate on Dissolution of Paracetamol Extended Release Bilayer Tablets - ทิพย์ทินกร ธวัชชัย; ฉาบกังวาล พัชรพล; กิตติธีระกูร สุธาธิป (Journal of Health Sciences and Wellness, 2019)
The objective of this research was to study the effect of sodium starch glycolate on dissolution of paracetamol extended release bilayer tablets. The immediate and extended release layers were prepared by wet granulation method. Extended release layer was prepared by using hydroxypropyl methylcellulose K4M (HPMC K4M) as matrix former at 1.25% of extended release layer weight. Sodium starch glycolate was used as disintegrant with concentrations 0, 1, 1.5, 2 and 2.5% of extended release layer weight. In vitro released studies were performed according to dissolution USP 40 and compared with dissolution specification. The results showed that the released rate increased with increased of sodium starch glycolate. The dissolution profile of the drug with 1.5% sodium starch glycolate was similar to that of the innovator. Both were conformed to the acceptance criteria level L1 of USP 40. Dissolution test results were further analysis by comparing with the innovator. The values of difference factor ( ) and similarity factor ( ) were 4 and 68, respectively. Drug released kinetics was followed Fickian diffusion. The mechanism of drug released through the matrix was found to be diffusion swollen and erosion controls. Extended release layer with HPMC K4M 1.25% as matrix former and sodium starch glycolate 1.5% as disintegrant would be benefit for this study. Therefore, the extended released bilayer tablets could be a potential dosage form for delivering paracetamol